Phytotoxicity of Solanum aculeatissimum Jacq: leaves extract - Silva, Regildo Márcio Gonçalves da [UNESP]; Merle, Paulo José Rodrigues [UNESP]; Martins, Gustavo Rafagnin [UNESP]; Mecina, Gustavo Franciscatti [UNESP]; Santos, Pamela Cristina dos [UNESP]; Santos, Valter Henrique Marinho dos [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Peixoto, Erika Cosendey Toledo de Mello; Silva, Luciana Pereira da (My University, 2015)
The objective of this study was to evaluate the phytotoxicity of Solanum aculeatissimum Jacq. leaves ethanolic extract in seeds germination, development and fixation of Lactuca sativa seedlings. The same study also aimed to assess the mitotic index of lettuce roots meristematic cells, quantification of phenols and total flavonoids and triage by mean of phytochemical testing of the main secondary metabolites classes. Bioassays of germination, development of root and hypocotyl were carried out in Petri dishes using achenes of Lactuca sativa L. cv. 'Grand Rapids' (lettuce). Concomitantly, were evaluated the physico-chemical characteristics (pH, osmotic potential and electrical conductivity), mitotic index, quantification of total phenols and flavonoids and determination of phytochemical profile of the treatments extract. The results obtained in the bioassays demonstrate that the ethanol extract of S. aculeatissimuma presents phytotoxic potential in the development of lettuce seedlings, given that the concentration of 20 mg/ml showed greater inhibition (41% of germination). The extract contains significant amounts of antioxidants, total flavonoid and phenols, where the concentration 1000µg/mL showed higher values (86.50%). Furthermore, it was possible to observe the presence of compounds with allelopathic activity in the phytochemical screening test as coumarins, tannins, terpenes, flavonoids and alkaloids. Given the above it is clear that the ethanolic extract of S. aculeatissimum presents allelopathic substances with phytotoxic activity that can affect the germination and development of other plant species in their natural environment.
Keywords: Allelopathy; antioxidants; 1,1-diphenyl-2-picrylhydrazyl (DPPH) test; Lactuca sativa